2021
DOI: 10.5267/j.msl.2020.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting employees’ motivation

Abstract: This study primordially aimed at determining the effects of different factors affecting employee’s motivation at Groz-Beckert Vietnam Co. Ltd. Upon perusal and review of related literature, the researchers found out that there is a dearth of studies that have been conducted relative to this subject appertaining to MNCs in Asian countries. Thus, this paper intends to provide empirical evidences towards the link between and among selected variables being covered in this study. The researchers used the quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…This finding supports Berkson et al (2012) but rejects Yusoff et al (2013). Also, the finding is in line with Owoyele (2016), Bawa (2017), Uzonna (2013), and (Le et al 2021).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This finding supports Berkson et al (2012) but rejects Yusoff et al (2013). Also, the finding is in line with Owoyele (2016), Bawa (2017), Uzonna (2013), and (Le et al 2021).…”
Section: Resultssupporting
confidence: 86%
“…The researcher, however, has not found any research studies concerning this problem at academic and business organizations in Nepal. Upon observation and review of previous literature, the researchers revealed that there is a dearth of research studies that have been performed on this issue concerning MNCs in Asian countries (Le et al 2021). The problem toward which the study is directed is to explore the following research questions:…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with Qarri and Fejza (2018) working conditions as motivation for employees. This result is also in line with Le et al (2021) and Lu et al ( 2021) that working conditions influence work motivation. For further research, it is recommended to examine how to maintain employee motivation to work in hotels with good performance.…”
Section: The Effect Of Work Condition Toward Hotel Management Graduates Work Motivation In the Hotel Industry During The Covid-19 Pandemisupporting
confidence: 92%
“…A properly motivated employee can work more effectively than an unmotivated one (Olexová and Gajdoš 2016;Vlacseková and Mura 2017;Stachová et al 2018). According to Le et al (2021), there are a lot of factors affecting employee motivation. Vávra et al (2021) found seven basic motivational factors i.e.…”
mentioning
confidence: 99%